PERAN SERTA MASYARAKAT DALAM MENSOSIALISASIKAN PONDOK PESANTREN DARUT TAFSIR - Kholidatunur Kholidatunur (Jurnal Manajemen Pendidikan, 2013)
This study attempts to examine and analyze in detail the role of the community in disseminating the Darut Tafsir Islamic Boarding School at the city of Bogor, West Java. For more details, this study examines in detail on "how to promote community participation in Darut Tafsir Islamic Boarding School?", Which focused on: 1) community participation in boarding school socialization planning, 2) community participation in boarding school socialization leading, 3) community participation in boarding school socialization controlling. This study will use a qualitative approach and methods used in this study is the case study method. It will be discussed in this study are: Firstly, community participation in socialization boarding school planning, consisting of: a) community participation in socialization planning, b) the way to involve the community participation in socialization planning, c) community participation in the process of socialization planning. Secondly, community participation in boarding school socialization leading, consisting of: a) community participation in socialization leading, b) the way to involve the community participation in socialization leading, c) community participation in the process of socialization leading. And thirdly, community participation in boarding school socialization controlling, consisting of: a) community participation in socialization controlling, b) the way to involve the community participation in socialization controlling, c) community participation in the process of socialization controlling.